When does team remuneration work? An experimental study on interactions between workplace contexts - Simon Bartke; Felix Gelhaar (Kiel Institute for the World Economy (IfW), 2018)
The extent to which individuals cooperate depends on the context. This study analyzes how interactions of workplace context elements affect cooperation when free-riding is possible. Context consists of a novel team building exercise, varying degrees of complementarity in production, and different remuneration schemes. After participation in the team building exercise and when complementarities are high, subjects exert higher efforts under team remuneration than under individual remuneration, despite the possibility to free-ride. Across all contexts, subjects cooperate significantly more than Nash equilibria predict. Compared to contexts in which not all contextual elements are cooperatively aligned, cooperation in a cooperative context relies significantly less on beliefs and personal values. Instead, a cooperative context changes how a subject's achievement motivation influences cooperation. Our findings present insights on how preferences react to context interactions and how these reactions enable organizations to use team incentives.
Keywords: D2; D91; L23; M14; M52; 330; team building; workplace context; laboratory experiment; stability of preferences; motivation; cooperation